Determinants of Tax Revenue Through the Effectiveness of Tax Audit as an Intervening Variable - BARRETO, Carlos Afonso (PT Keberlanjutan Strategis Indonesia, 2025)
The contribution of tax audit results to tax revenue in Timor-Leste remains very low, averaging only 3.25% over the past four years. This has prompted further analysis of the factors determining the effectiveness of tax audits in order to enhance tax revenue. The study employs a survey approach using questionnaires as the data collection instrument and applies Partial Least Squares–Structural Equation Modeling (PLS/SEM) for analysis. The independent variables include the quality of tax auditors, the quantity of tax auditors, facilities and infrastructure, and financial compensation. The mediating variable is tax audit effectiveness, and the dependent variable is tax revenue. Results from direct effect testing show that the variables of auditor quality and facilities/infrastructure have a positive but insignificant effect on tax revenue. Meanwhile, the quantity of tax auditors and their financial compensation has a negative but insignificant effect on tax revenue. However, the effectiveness of tax audits has a significant positive effect on tax revenue. The indirect effect analysis reveals that auditor quality, auditor quantity, and financial compensation—through tax audit effectiveness—have a significant positive influence on tax revenue, whereas facilities and infrastructure have a positive but insignificant effect.